Prognostic factors associated with mortality in patients with severe alcoholic hepatitis - Ana Bargalló García; Isabel Serra Matamala; Ingrid Marin Fernández; Helena Masnou Ridaura; Carlos Leal Valdivieso; Pilar Marcos Neira; Marga Sala Llinars; Rosa Morillas Cunill; Ramón Planas Vila (Revista Espanola de Enfermedades Digestivas, 2013)
Severe alcoholic hepatitis is associated with high early mortality. This study aimed at identifying prognostic factors associated with in-hospital, medium- and long-term mortality of severe alcoholic hepatitis and to evaluate the different prognostic scoring systems on a cohort of patients in our hospital. To this end, we conducted a retrospective analysis of 66 episodes admitted between 2000 and 2008. Clinical and laboratory data on admission, at 7 days, 1 month, 6 months, and after one year were collected and analyzed, as were the details on the treatment and complications that occurred during hospitalization; the different prognostic indices used in the literature were calculated. Death event associated with an episode of severe alcoholic hepatitis occurs primarily during the first month, with an average mortality rate of 16.9. Infectious complications were associated with lower in-hospital survival. MELD score, urea and bilirubin values one week after admission were independently associated with both in-hospital survival (OR = 1.14, 1.012 and 1.1, respectively), and survival at 6 months (OR = 1, 15; 1.014 and 1.016, respectively). Only MELD score and urea values at 7 days were independent predictors of survival twelve months after the acute hepatitis episode. MELD score, urea, and bilirubin 7 days after admission were the only independent in-hospital survival and also long-term survival factors 6 months and one year after the episode. In our cohort, the MELD score was the best prognostic index to predict mortality associated with an episode of severe alcoholic hepatitis.